Brief Report: Persistence of Non-Vaccine Oncogenic HPV Genotypes in Quadrivalent HPV-Vaccinated Women Living With HIV. (1st March 2020) - McClymont, Elisabeth; Coutlée, François; Lee, Marette; Albert, Arianne; Raboud, Janet; Walmsley, Sharon; Lipsky, Nancy; Loutfy, Mona; Trottier, Sylvie; Smaill, Fiona; Klein, Marina B.; Yudin, Mark H.; et al.
Abstract : Background: Human papillomavirus (HPV) vaccines have promising safety and immunogenicity data in women living with HIV (WLWH). However, it is critical to understand the residual burden of oncogenic HPV within WLWH to inform postvaccination cervical screening needs. We assessed rates of persistent infection with nonquadrivalent HPV (qHPV) oncogenic types in a cohort of qHPV-vaccinated WLWH. Setting: Multicentre, longitudinal cohort across Canada. Methods: WLWH were scheduled to receive 3 doses of qHPV vaccine. Participants provided health data and HPV DNA samples. Persistent cases of HPV were defined as new HPV in samples from ≥2 consecutive visits or as HPV present in the last sample. HPV31/33/35/39/45/51/52/56/58/59/68/82 were considered to have oncogenic potential. Median follow-up time was 4 years after initial vaccine dose. Results: A total of 284 participants were eligible for this analysis with 1205 person-years (PY) of follow-up (≥1 dose of vaccine, ≥1 HPV DNA result after vaccination). The highest incidence of persistent infection was with HPV51 (1.38/100 PY), followed by HPV52 (1.18/100 PY), and HPV39 (1.06/100 PY). The incidence of persistent infection with pooled HPV types added in the nonavalent vaccine (HPV31/33/45/52/58) was lower than the incidence of persistent oncogenic HPV types not contained within available vaccines (HPV35/39/51/56/59/68) (2.4/100 PY versus 3.6/100 PY, respectively). Conclusions: qHPV-vaccinated WLWH continue to face a burden of persistent oncogenic HPV infection. Although the nonavalent vaccine could alleviate some of this burden, 2 of the top 3 persistent oncogenic HPVs in this cohort are not contained within any available vaccine. This highlights the need for ongoing cervical screening in HPV-vaccinated WLWH.